System‐wide optimization of an orthogonal translation system with enhanced biological tolerance - Kyle Mohler; Jack M Moen; Svetlana Rogulina; Jesse Rinehart (Molecular Systems Biology)
Abstract Over the past two decades, synthetic biological systems have revolutionized the study of cellular physiology. The ability to site‐specifically incorporate biologically relevant non‐standard amino acids using orthogonal translation systems (OTSs) has proven particularly useful, providing unparalleled access to cellular mechanisms modulated by post‐translational modifications, such as protein phosphorylation. However, despite significant advances in OTS design and function, the systems‐level biology of OTS development and utilization remains underexplored. In this study, we employ a phosphoserine OTS (pSerOTS) as a model to systematically investigate global interactions between OTS components and the cellular environment, aiming to improve OTS performance. Based on this analysis, we design OTS variants to enhance orthogonality by minimizing host process interactions and reducing stress response activation. Our findings advance understanding of system‐wide OTS:host interactions, enabling informed design practices that circumvent deleterious interactions with host physiology while improving OTS performance and stability. Furthermore, our study emphasizes the importance of establishing a pipeline for systematically profiling OTS:host interactions to enhance orthogonality and mitigate mechanisms underlying OTS‐mediated host toxicity.